Investigation of Heat Transfer Enhancement Mechanisms in Elastic Tube Bundles Subjected to Exogenous Self-Excited Fluid Oscillation - Jing Hu; Lei Guo; Shusheng Zhang (Fluids)
Flow-induced vibration (FIV) characteristics are key factors in enhancing heat transfer. However, challenges such as insufficient heat transfer enhancement and the fatigue strength of the tube bundle persist in the context of improving the heat transfer in elastic tube bundle heat exchangers. This study proposes a novel passive heat transfer enhancement paradigm for elastic tube bundles based on externally induced self-excited oscillations of fluid. By constructing a non-contact energy transfer system, the external oscillation energy is directed into the elastic tube bundle heat exchanger, achieving dynamic stress buffering and breaking through the steady-state flow heat transfer boundary layer. A three-dimensional fluid–structure interaction numerical model is established using Star CCM+2021.3 (16.06.008) to conduct a comparative analysis of the flow characteristics and heat transfer performance between the original structure without an oscillator and the improved structure equipped with a fluid oscillator. The results indicate that the improved structure, through the periodic unsteady jet induced by the fluid oscillator, significantly enhances the turbulence intensity of the shell-side fluid, with the turbulent kinetic energy increasing by over 50%. The radial flow area is notably expanded, thereby reducing the thermal resistance of the boundary layer. At cooling fluid velocities of 6 to 9 m/s, the heat transfer capability of the improved structure is enhanced by more than 50%. Compared with the original structure, the new structure, due to the loading of an external oscillation structure, causes the cold air to present a periodic up and down jet phenomenon. This jet phenomenon, on the one hand, increases the heat exchange area between the cold air and the outer surface of the tube bundle, thereby enhancing the heat exchange capacity. On the other hand, the large-area impact of the fluid reduces the thickness of the boundary layer, lowers the thermal resistance and thereby enhances the heat exchange capacity. Furthermore, this improved structure buffers the mechanical vibrations through self-excited oscillations of the fluid medium, ensuring that the stress levels in the tube bundle remain below the fatigue threshold, effectively mitigating the failure risks associated with traditional active vibration strategies.